1988
DOI: 10.1523/jneurosci.08-12-04780.1988
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and characterization of three genes uniquely expressed in cerebellum by Purkinje neurons

Abstract: The characteristics that distinguish the different neuronal cell types of an organism are believed to be primarily determined by unique patterns of cellular gene expression. The identification of cell-type specific molecules should therefore provide a good basis for understanding the biology of specific neuron types. In this paper, we describe the isolation of cDNA clones corresponding to mRNA uniquely expressed by Purkinje cells in mature mouse cerebellum. Three cDNA clones were selected from a library of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 23 publications
1
90
1
Order By: Relevance
“…However, Nordquist et al [22] reported that in testis the intensity of mRNA bands hybridizing to PCD6 clone, which is part of the IP3 receptor cDNA, appeared to be almost the same as that in kidney tissue. With regard to this discrepancy, we believe that the testis preparation of Nordquist et al [22] contained the ductus deferens (= vas deferens) which is composed of smooth muscle, while our preparation did not. In ovary sections (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…However, Nordquist et al [22] reported that in testis the intensity of mRNA bands hybridizing to PCD6 clone, which is part of the IP3 receptor cDNA, appeared to be almost the same as that in kidney tissue. With regard to this discrepancy, we believe that the testis preparation of Nordquist et al [22] contained the ductus deferens (= vas deferens) which is composed of smooth muscle, while our preparation did not. In ovary sections (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…We cut 12-14 10-m thick sagittal sections at 200-m intervals from the midline, and performed in situ hybridization with probes specific for Pcdha1, Pcdha10, Pcdha12, Pcdhac1, Pcdhac2, and Purkinje cell protein 2 (Pcp2) (41). The sections were then photographed with a BIOREVO BZ-9000 microscope (Keyence).…”
Section: R/g16neomentioning
confidence: 99%
“…Some genes are highly specific to certain neuron subpopulations (1,2), whereas others, especially isoenzymes of the general metabolism, are expressed in any types of neurons, although at different levels (3,4). The aldolase C gene, coding for the brain-specific form of the glycolytic enzyme aldolase, belongs to this last class and, in addition, is also transcribed in glial cells (5,6).…”
mentioning
confidence: 99%
“…Like other genes broadly expressed in the brain, the aldolase C gene exhibits several features of housekeeping genes, namely the absence of canonical TATA and CAAT boxes, GC-rich sequence, and multiple transcription start sites (3,4,(7)(8)(9). We have previously reported that brain-specific expression of the CAT 1 reporter gene in transgenic mice could be directed by a short (Ͻ115 bp) promoter fragment of the aldolase C gene (10); however, this short fragment was not able to direct the high level transgene expression observed with the full-length 5.5-kb 5Ј-flanking region (11,12). To identify DNA regulatory elements required to ensure high level gene expression in the brain, we have now defined in vivo, in transgenic mice, activating sequences of the aldolase C gene and some of the cognate DNA-binding transcription factors.…”
mentioning
confidence: 99%